Pengaruh Jumlah Nozel Distributor Terhadap Kinerja Fluidized Bed Gasifier - Elis Saputra, Riski; , Nur Aklis, S.T., M.Eng (2017)
The burning of gas fuel is more profitable than solid fuel because it produces a cleaner combustion, gas products can be made by way of a fluidized bed gasifier with rice husk fuel. This research aims to know the influence of the number of nozzles distributor fluidized bed gasifier on performance at the speed of 1,3 m/s which include minimum speed fluidization, the reactor temperature,time effective flame and the influence of the amount of gas produced. The research began with the manufacture of tools of fluidized bed gasifier rice husk, then do the test firing by setting the air distributor number of nozzle 3, nozzle 5, nozzle 7. The data measured in this research is to measure the speed of a minimum fluidization, reactor temperature, influences the amount of gas produced from the time effective flame. The results showed the number of nozzles on a distributor appliance affect the performance of fluidized bed gasifier the greater number of nozzles the minimum speed that produced the lower number 7 nozzles of 0,9 m/s . For the highest temperature is obtained from the distributor number of nozzles 7 of 465,5ºC. While for the longest time effective flame distributor 3 nozzles amount obtained during the 65 minute. The amount of gas produced is the largest distributor of the number of nozzles 7 of 1561.4269 Kj.